Merdeka atas Konflik: Membangun Teologi Konflik Berdasarkan Konflik Filemon dengan Onesimus dalam Surat Filemon - Putra, Adi (Sekolah Tinggi Teologi Sumatera Utara, 2025)
Conflict is an unavoidable reality, even within the church, which often becomes trapped in internal disputes. This situation necessitates a biblical theological model for conflict resolution. This research aims to construct a theology of conflict based on an analysis of the Epistle to Philemon, specifically focusing on the conflict between Philemon and Onesimus. Using a qualitative method through a literature review and biblical exegesis, this study examines the conflict resolution strategy employed by the Apostle Paul. The findings indicate that Paul did not merely mediate but implemented a transformative, Gospel-centered approach, which included persuasive communication, assumption of responsibility, and total forgiveness that changed the relationship from master-slave to brothers in faith. This concept is formulated as